ANALISA KUALITAS PRODUK TAHU DI CV. IKHWANUDIN DI DESA JOROK SUMBAWA BESAR DENGAN METODE VOICE OF CUSTOMER(VOC) - Ismi Mashabai; Suryani; ilham kurnia sakti lubis; Agung Gumelar (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2021)
Research has an important role in the world of education and is useful in obtaining new knowledge from a product. The role of this research provides benefits to the CV tofu factory. Ikhwanudin in JorokSumbawa Besar Village to produce tofu with better quality and selling value than before. The large number of industrial competitors requires Pak Ikhwanudin to be able to choose good quality soybeans as the raw material for making tofu. Good tofu has the criteria of a dense texture, does not have a sour smell, has a perfect appearance, and has a good taste. The quality of the tofu varies greatly due to different clumping materials and different manufacturing processes. Tofu is produced by utilizing the properties of protein, which will clot when reacting with acids. One of the research methods used in this research is the Voice of Customer (VoC) method. Quality control with this method is carried out by identifying the types of product defects / defects so that in the end, the defects can be minimized and through the voice of consumers, the producers will know what the shortcomings of tofu products have been sold so that they can be used as improvements in the future.